Analisis Strategi Digital Marketing Sekolah dalam Meningkatkan Citra Institusi Sekolah: Studi Kasus pada SMA Budhi Warman 2 Jakarta - Faried, Ade Achmad; Adiba; Aziz, Danang (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This research aims to analyze the digital marketing strategies implemented by SMA Budhi Warman 2 Jakarta through social media, the challenges faced, and its impact on institutional image. A descriptive qualitative approach was used with data collection techniques including interviews, observation, and documentation. The results show that the school has utilized various digital platforms such as Instagram, Facebook, TikTok, YouTube, and an official website for promotion and public communication. However, several challenges remain, including limited content production tools, non-professional human resources, and high competition from other schools. Digital marketing strategies have positively impacted the increase in PPDB applicants, public interaction, and a shift in public perception of the school as a modern and innovative institution. Recommendations include forming a dedicated digital marketing team, conducting regular training, developing an annual content calendar, and implementing periodic evaluations.   Keywords: digital marketing, school branding, institutional image, social media, Integrated Marketing Communication.